Perbedaan Keintiman Keluarga Antara Wanita Pekerja Shift Malam Dan Ibu Rumah Tangga Di Kecamatan Kartasura - Akbar, Muhammad Taufan; , dr. Yusuf Alam Romadhon, M.Kes; , dr. Listiana Masyita Dewi, M.Sc (2015)
Background: International Institute of Population Science in Indonesia showed that there are more than 40% of women running multiple functions, such as raising the child while working. Family intimacy has a big predictive ability in marital satisfaction. Intimacy can stated as marital satisfaction predictors. Intimacy between men and women positively correlated marital satisfaction it also means that intimacy night shift female workers are not only run their functions as a housewives but also as a breadwinner. Objective: This study aims to determine whether there are differences family intimacy between night shift female workers and housewives in the district of Kartasura. Methods: Design research using analytic observational, by cross-sectional approach. The number of survey respondents was 64 respondents. The sampling technique used purposive sampling. The level of intimacy measured by questionnaire Muchlas & Sudiyanto family intimacy. Data were analyzed by chi-square hypothesis test in SPSS 17.0 for Windows. Result: The results showed that the p value = 0.000 ( p < 0.05 ), which indicates that there are differences family intimacy between night shift female workers and housewives to force a significant difference. Conclusion: There was difference of family intimacy between night shift female workers and housewife in district of Kartasura. The level of intimacy housewife is better than night shift female workers.